Lithium vapor cave design considerations - E.D. Emdee; R.J. Goldston (Nuclear Materials and Energy)
Recent calculations of the lithium vapor box divertor using SOLPS have demonstrated that far Scrape-Off Layer (SOL) baffling and the corresponding far SOL lithium evaporation are unnecessary for divertor performance. The plasma, acting as a virtual baffle, is sufficient to block the neutral lithium from escaping the divertor region in a configuration known as the lithium vapor “cave.” Here, extensions of this PFC design simplification are presented which show that significantly less obtrusive PFCs can provide similar divertor performance. Differences in upstream concentration are predicted depending on the depth and size of the lithium emitting aperture, the shape of the private flux region (PFR) structure, and the location within the PFR of the deuterium puff. SOLPS predictions for (nLi/ne)LCFS vary between 0.020 and 0.049. For the first time, the effect of E×B drifts on predictions for a lithium vapor box divertor is also examined, with the resulting solutions having lower inner divertor heat flux but higher outer divertor heat flux for a given lithium evaporation rate. The differences between the PFC designs are minimized with drifts enabled, indicating design flexibility. The increased PFC design flexibility reported here, along with improved SOLPS modeling with drifts, are important steps towards a final design.